ЩОДО ПИТАННЯ ПІДВИЩЕННЯ КОЕФІЦІЄНТА ПОТУЖНОСТІ ОДНОФАЗНОГО ДЖЕРЕЛА ЖИВЛЕННЯ МАШИН КОНТАКТНОГО ЗВАРЮВАННЯ - Поднебенна, С.К.; Бурлака, В.В.; Гулаков, С.В. (Інститут електродинаміки Національної академії наук України, 2017)
This work aims to resistance welding machine’s power supplies power factor’s increasing. This is achieved by reducing of reactive power consumption. The disadvantages of resistance welding machine’s thyristor-based power supplies, are considered. The factors that caused these disadvantages were analyzed. Application of transistor-based power supply to resistance welding machine was considered. This power supply realized not only leading-edge modulation, like thyristor-based power supply, but trailing-edge modulation too, thus allowing to control the input current during the mains period. This allows to control of power supply’ active and reactive power. Unlike the thyristor-based power supply, transistor-based power supply can work in both modes: in VAR consumption mode and VAR generation mode. This makes possible to allow VAR power compensation by using transistor-based power supply in conjunction with thyristor-based power supply. References 11, figures 8, table.